2017
DOI: 10.1038/s41598-017-09706-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxalate ligand functionalization on Co/ZSM-5 activity in Fischer Tropsch synthesis and hydrodeoxygenation of oleic acid into hydrocarbon fuels

Abstract: Achieving high degree of active metal dispersions at the highest possible metal loading and high reducibility of the metal remains a challenge in Fischer Tropsch synthesis (FTS) as well as in hydrogeoxygenation (HDO).This study therefore reports the influence of oxalic acid (OxA) functionalization on the metal dispersion, reducibility and activity of Co supported ZSM-5 catalyst in FTS and HDO of oleic acid into paraffin biofuel. The Brunauer–Emmett–Teller (BET) results showed that cobalt oxalate supported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…61 This was explained by the increased reducibility in the active metal site. Some authors have worked to elucidate the effect of particle localization, whether in the external surface of the support 61,131 or inside the pores, 83,116,132 on catalytic performance. Yao et al 61 and Lu et al 130 have demonstrated that the catalyst synthesis method has a significant effect on metal particle localization, with the PEG additive method resulting in the deposition of most Co 3 O 4 particles on the outer surface of ZSM-5, which increases the metal reducibility (up to 31%).…”
Section: ;mentioning
confidence: 99%
“…61 This was explained by the increased reducibility in the active metal site. Some authors have worked to elucidate the effect of particle localization, whether in the external surface of the support 61,131 or inside the pores, 83,116,132 on catalytic performance. Yao et al 61 and Lu et al 130 have demonstrated that the catalyst synthesis method has a significant effect on metal particle localization, with the PEG additive method resulting in the deposition of most Co 3 O 4 particles on the outer surface of ZSM-5, which increases the metal reducibility (up to 31%).…”
Section: ;mentioning
confidence: 99%
“…H 2 -TPR ( Fig. 2) revealed the main reduction peaks at temperatures lower than 400 °C which are ascribed to the reduction of Co 3 O 4 that proceeds via a multistep mechanism (reduction of Co 3 O 4 to CoO and then to metallic Co) [29,30].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Noted, the OA conversion also even higher than former finding (83%) [46], implying the high OA conversion rate was attributed to the elevated reaction temperature (300-400 °C). Overall, HZSM5 demonstrated lesser OA conversion, possibly due to its lower acidity and existence of strong acid sites which tends to adsorb strongly the oxygenated species, resulting in total coverage of HZSM5 active species [47]. A high coverage of oxygenates species reduces HZSM5 HDO activity and consequently OA conversion.…”
Section: Catalytic Activity Performancementioning
confidence: 99%